Avaliação da disponibilidade de iluminação natural em salas de aula de instituição de ensino superior - Tamiosso, Cíntia Dornelles Pereira (2015)
Visual comfort conditions in school buildings are important to provide well-being, health and improving educational productivity. Considering benefits that visual comfort promotes, this research aimed to evaluate the daylight availability for two classrooms in a high school located in interior of Rio Grande do Sul, southern Brazil. The analysis was based on two methods. One of them considered in situ measurements of illuminance levels with datalogger during five days on April, June, August and December (twenty days of measurements), according to NBR 8995 Brazilian standard; the other considered the students momentary satisfaction with natural light quality through the application of questionnaires with face-to-face direct questions in one day for mentioned months. Further the artificial and natural lighting requirements according to RTQ-C Brazilian standard were verified. The natural light factor (CIN) was calculated based on internal and simultaneous external illuminances obtained through measurement with a manual luximeter. The method used to find CIN was based on NBR 15215-3 Brazilian standard. Taking into account measurement period the illuminance levels were higher than standard values stablished on NBR 8995 for the majority of measured points. The study also showed that the majority of students were satisfied with momentary light conditions available in classrooms. They reported problems with direct solar radiation on desks. The light system of analyzed classrooms did not satisfy the requirements of RTQ-C referring to automatic artificial light controls. The CIN coefficients presented high variability that demonstrates the regional daylight also presents heterogeneous conditions throughout the year. The main findings are the difficulty of defining a suitable method to measure external illuminances in situ, CIN references for specific Brazilians sky conditions and difficulty of measuring internal illuminances during long-range time due to high variability of regional cloudy and clear-sky conditions.